Analisis Hukum Terhadap Produk Makanan Tanpa Label Halal di Industri Rumah Tangga - Afdhila Nurukusuma; Jumailah (el hisbah: Journal of Islamic Economic Law, 2022)
The Law on Halal Product Assurance Number 33 of 2014 has mandated that all food products circulating in Indonesia must be certified halal. However, the fact is that in Pecangakan Village, Pemalang Regency, many home industries have not been certified halal, including the rambak cracker industry. Therefore, the purpose of this study is to find out how the legal provisions related to food products must be certified halal, and to find out the legal impact of food products that have not been certified halal. This research is an empirical legal research with qualitative method and sociological approach. The results of the study show that the halal label for food products is one of the things mandated by Law Number 33 of 2014 concerning Halal Product Guarantee and Law Number 39 of 2021 concerning the Implementation of the Halal Product Assurance Sector. Whereas in Islamic law, halal certification of food products is not mandatory. The legal impact of the rambak cracker industry that has not been certified halal is contrary to the mandate of Law Number 33 of 2021, so that producers can be subject to sanctions. Meanwhile, if from the perspective of Islamic law, the cracker rambak industry in Pecangakan Village does not include a halal label, there are no legal consequences for this action.